Sociodemographic and clinical functional factors in pre-frail and frail older adults with type 2 Diabetes Mellitus in relation to low levels of physical activity - Fernandes,Ana Clara Teixeira (2020)
Abstract Objective: To determine the sociodemographic and clinical-functional factors related to low levels of physical activity in pre-frail and frail older adults with type 2 diabetes mellitus (DM2). Method: an observational, analytical, cross-sectional study was performed. The sample consisted of older adults aged 60 years or over with a clinical diagnosis of DM2 who were treated at the Onofre Lopes University Hospital (or HUOL). Sociodemographic and clinical-functional data were evaluated with the following instruments: the Timed Up and Go (TUG) test, the Mini Mental State Examination (MMSE), the 15-item Geriatric Depression Scale (GDS), the International Physical Activity Questionnaire (IPAQ) and the frailty phenotype. The Chi-square and Mann Whitney tests were used for data analysis. Results: the study sample consisted of 113 individuals classified as pre-frail (52.2%) and frail (47.8%). Low levels of physical activity were verified in 79.6% of the sample. The most closely related variables that showed a statistically significant difference with low levels of physical activity were: years of schooling (p=0.02), social participation (p=0.005), insulin therapy (p=0.02), pain in the lower limbs (p=0.03) and depressive symptoms (p=0.04). Also, significant differences were found between low levels of physical activity and age (p=0.04) and years of schooling (p=0.05). Conclusions: Low levels of physical activity are associated with certain sociodemographic and clinical-functional factors, some of which are modifiable. Identifying these is important for the development of appropriate health interventions for the prevention and treatment of both DM2 and the Frailty Syndrome (FS).